Neutrino mixings and the S4 discrete flavour symmetry. Issue 4 (5th November 2012) - Bazzocchi, F.; Merlo, L.; Morisi, S.; Nilles, H.P.; Valle, J.W.F.
Abstract Discrete non‐Abelian Symmetries have been extensively used to reproduce the lepton mixings. In particular, the S4 group turned out to be suitable to describe predictive mixing patterns, such as the well‐known Tri‐Bimaximal and the Bimaximal schemes, which all represent possible first approximations of the experimental lepton mixing matrix. We review the main application of the S4 discrete group as a flavour symmetry, first dealing with the formalism and later with the phenomenological implications. In particular, we summarize the main features of flavour models based on S4, commenting on their ability in reproducing a reactor angle in agreement with the recent data and on their predictions for lepton flavour violating transitions.